Compassion organizing: Employees' satisfaction with corporate philanthropic disaster response and reduced job strain. Issue 2 (17th October 2014) - Watkins, Marla Baskerville; Ren, Run; Umphress, Elizabeth E.; Boswell, Wendy R.; Triana, María del Carmen; Zardkoohi, Asghar
Abstract : The literature on corporate social responsibility and corporate philanthropy generally focuses on how employers come to the aid of those outside the organization who have been affected by disasters. Less is known about an organization's corporate philanthropic disaster response (CPDR) directed towards their employees. We argue, based on conservation of resources (Hobfoll, 1989, Am . Psychol ., 44, 513) and compassion organizing (Dutton et al ., 2006, Admin . Sci . Quart ., 51, 59) literatures, that employees perceive employers who provide aid to them following a natural disaster as supportive. This aid from CPDR provides support to employees and helps to restore the loss of valued resources. Accordingly, we predict that satisfaction with CPDR reduces employee psychological and physiological strain via its positive effects on perceived organizational support. We find support for our predictions using a sample of 695 Hurricane Katrina survivors. Finally, we discussed theoretical contributions and implications of this research. Practitioner points: Organizations are encouraged to fulfil their social responsibilities. Our research shows that organizations should be socially responsible not only to the general public, but also to their own employees. Responding compassionately by providing aid to an organization's own employees is an important element in carrying out their social responsibilities. In the aftermath of a severe natural disaster, employees may need to rely on their organizations to provide timely assistance. Such assistance could help them mitigate their strain, both psychologically and physiologically, aroused from the disaster they experienced. Organizations' compassion organizing in the form of philanthropic disaster response to their employees may be beneficial to the organization. First, it shows the organization's intention to fulfil their social responsibility and to be a good and ethical citizen. Second, by providing assistance to their employees to deal with the challenge of restoring normal lives, organizations can help employees to continue working in a productive and effective way.